Randomized clinical trial of 24 versus 72 h antimicrobial prophylaxis in patients undergoing open total gastrectomy for gastric cancer. Issue 2 (January 2017) - Takagane, A.; Mohri, Y.; Konishi, T.; Fukushima, R.; Noie, T.; Sueyoshi, S.; Omura, K.; Ono, S.; Kusunoki, M.; Mochizuki, H.; Sumiyama, Y.
Abstract: Background: Open total gastrectomy carries a high risk of surgical‐site infection (SSI). This study evaluated the non‐inferiority of antimicrobial prophylaxis for 24 compared with 72 h after open total gastrectomy. Methods: An open‐label, randomized, non‐inferiority study was conducted at 57 institutions in Japan. Eligible patients were those who underwent open total gastrectomy for gastric cancer. Patients were assigned randomly to continued use of β‐lactamase inhibitor for either 24 or 72 h after surgery. The primary endpoint was the incidence of SSI, with non‐inferiority based on a margin of 9 percentage points and a 90 per cent c.i. The secondary endpoint was the incidence of remote infection. Results: A total of 464 patients (24 h prophylaxis, 228; 72 h prophylaxis, 236) were analysed. SSI occurred in 20 patients (8·8 per cent) in the 24‐h prophylaxis group and 26 (11·0 per cent) in the 72‐h group (absolute difference −2·2 (90 per cent c.i. −6·8 to 2·4) per cent; P < 0·001 for non‐inferiority). However, the incidence of remote infection was significantly higher in the 24‐h prophylaxis group. Conclusion: Antimicrobial prophylaxis for 24 h after total gastrectomy is not inferior to 72 h prophylaxis for prevention of SSI. Shortened antimicrobial prophylaxis might increase the incidence of remote infection. Registration number: UMIN000001062 (http://www.umin.ac.jp ). Abstract : 24h as good